Thermal response of tissue to RF exposure from canonical dipoles at frequencies for future mobile communication systems - K. Foster; D. Colombi (Electronics Letters)
The level of protection against thermal hazard of the current RF EM field (EMF) exposure limits is estimated at the transition frequency where the basic restrictions change from specific absorption rate to power density. It is shown that the calculated steady‐state temperature increase in the skin generated by a nearby dipole transmitting at maximum power to meet compliance with the EMF limits presents a significant discontinuity at this frequency. The results suggest that for exposure to limited areas of the body at frequencies where basic restrictions are provided in terms of power density, the currently existing exposure guidelines need to be revised. These findings might have large implications on the development of future radio access technologies operating at the millimetre wave.